PRODUCTION MANAGEMENT OF THE NORTH SUMATRA NEWS PROGRAM TODAY ON TVRI NORTH SUMATRA - Goenersya Haidar Rudhani; Abdul Rasyid (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines how TVRI North Sumatra manages the daily television news program “Sumatera Utara Hari Ini” amid digital-era demands for fast yet accurate local reporting. It focuses on how the station organizes pre-production, production, and post-production, and how internal communication and gatekeeping shape editorial and technical coordination. Using a qualitative descriptive case study, data were gathered during a one-month field placement through participant observation, semi-structured interviews with key production roles (including CG and MCR), and documentation review, then analyzed thematically. Findings show a workflow supported by regional coordinators who often act as reporter–camera operators, flexible rundown filling (about 22 items), and intensive script editing to align text–visuals and manage timing (packages typically 1–2.5 minutes). Post-production centers on clean-feed recording, quality checks, archiving, and digital republishing. Overall, consistent cross-role communication functions as the main control mechanism to prevent mismatches and keep broadcasts ready to air.